Genotyped cluster investigations versus standard contact tracing: comparative impact on latent tuberculosis infection cascade of care in a low-incidence region - Michael Asare-Baah; Marie Nancy Séraphin; LaTweika A.T. Salmon-Trejo; Lori Johnston; Lina Dominique; David Ashkin; Krishna Vaddiparti; Awewura Kwara; Anthony T. Maurelli; Michael Lauzardo (BMC Infectious Diseases)
Abstract Background Cluster and contact investigations aim to identify and treat individuals with tuberculosis (TB) and latent TB infection (LTBI). Although genotyped cluster investigations may be superior to contact investigations in generating additional epidemiological links, this may not necessarily translate into reducing infections. Here, we investigated the impact of genotyped cluster investigations compared to standard contact investigations on the LTBI care cascade in a low incidence setting. Methods A matched case-control study nested within a cohort of 6,921 TB cases from Florida (2009–2023) was conducted. Cases (n = 670) underwent genotyped cluster investigations, while controls (n = 670) received standard contact investigations and were matched 1:1 by age. The LTBI care cascade outcomes were compared using Pearson’s chi-square tests. Results Of the 5,767 identified contacts, 3,230 (56.0%) were associated with the case group, while 2,537 (44.0%) were identified in the control group. A higher proportion of contacts were evaluated in the control group (85.5%) than in the case group (81.5%, p < 0.001). While the proportion of evaluated contacts diagnosed with LTBI did not significantly differ between the groups (case: 20.4%, control: 21.5%, p = 0.088), a higher percentage of LTBI-diagnosed contacts initiated TB preventive treatment (TPT) in the control group (95.9%) than the case group (92.9%, p = 0.029). TPT completion rates were similar, with 65.2% in the case group and 66.3% in the control group (p = 0.055). TB patients in the case group were more likely to be males, U.S.-born, Asians, residents of long-term care or correctional facilities, with past year histories of alcohol use, homelessness, and drug use. Conclusion Despite the demographic and epidemiological differences between cases and controls, cluster investigations identified more contacts, with no significant difference in contacts diagnosed with LTBI, but were less effective than standard contact investigations in evaluating contacts, initiating LTBI treatment, and ensuring completion.